2011
DOI: 10.1073/pnas.1010241108
|View full text |Cite
|
Sign up to set email alerts
|

Land inheritance establishes sibling competition for marriage and reproduction in rural Ethiopia

Abstract: Intergenerational transfer of wealth has been proposed as playing a pivotal role in the evolution of human sibling relationships. Sibling rivalry is assumed to be more marked when offspring compete for limited heritable resources, which are crucial for reproductive success (e.g., land and livestock); whereas in the absence of heritable wealth, related siblings may cooperate. To date, comparative studies undertaken to support this evolutionary assumption have been confounded by other socioecological factors, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 39 publications
2
81
0
Order By: Relevance
“…Number of sisters, however, had a moderately positive effect on male fertility. Similar effects on the number of surviving offspring have been demonstrated on the Kenyan Kipsigis [33] and the Ethiopian Arsi Oromo [41]. Gillespie et al [34] found that large sibships reduced survival, but not fertility among survivors in eighteenth-to nineteenth-century Finland.…”
Section: Family Size and Offspring Success In Humans (A)mentioning
confidence: 54%
See 2 more Smart Citations
“…Number of sisters, however, had a moderately positive effect on male fertility. Similar effects on the number of surviving offspring have been demonstrated on the Kenyan Kipsigis [33] and the Ethiopian Arsi Oromo [41]. Gillespie et al [34] found that large sibships reduced survival, but not fertility among survivors in eighteenth-to nineteenth-century Finland.…”
Section: Family Size and Offspring Success In Humans (A)mentioning
confidence: 54%
“…Supporting this explanation, Voland & Dunbar [36] found that negative effects of large family size were unique to landowning families in the Krummhö rn, while for peasants, offspring success was determined by other means. Gibson and Gurmu [41] also shows that number of older brothers holds negative associations with marital and reproductive success (number of surviving offspring) in rural Ethiopian farmers only when land quality had been determined by inheritance from parents. In otherwise comparable men who received land allocations from a government redistribution scheme, the existence of older brothers had no negative consequences.…”
Section: (B) Socioecological Contextmentioning
confidence: 95%
See 1 more Smart Citation
“…Although the confidence bands are wide enough that a horizontal or upward-sloping regression line could be fitted, the line that best fits the data is negatively sloped. Details on individual data points may be found in [70][71][72][73][74][75][76][77][78][79][80][81][82]97,98].…”
Section: Box 1 Changing the Direction Of The Causal Arrow Between Pimentioning
confidence: 99%
“…Mean parity (live births) is 6.2 children (std dev 2.83). Mortality rates remain high but have been declining in recent decades (Gibson & Gurmu, 2011). Inheritance is patrilineal and husband and wife generally reside with the husband's patrilineage at marriage (patrilocal residence).…”
Section: Study Populationmentioning
confidence: 99%